ANALISIS KANDUNGAN KIMIA DAN SIFAT SERAT TANAMAN PURUN TIKUS (Eleocharis dulcis) ASAL KALIMANTAN SELATAN - Sunardi Sunardi (Bioscientiae, 2012)
Purun tikus (Eleocharis dulcis) is an aquatic plant which grows in greatamount in swamp lands in South Kalimantan. This research is conducted to findout chemical content and fiber properties to know the potential utilization of thisplants. The results showed that the water content of purun tikus plant is 92,68%,extractive in alcohol-benzena content is 9,53%, lignin content is 26.4%; and thecellulose content is 32,62%. The study of purun tikus fiber anatomy have beencompleted with the results of the fiber diameter is equal to 5.89 μm; lumendiameter is 2.68 μm, cell wall thickness is 1.61 μm and fiber length is 1.68 mm.The value of the derivative dimension of purun tikus fiber obtained as follows:runkel ratio is 1.2; mulstep number is 38.4 (%), power loom is 285.45, value offlexibility is 0.45 and stiffness coefficient is 0.27. All results suggested that puruntikus plants offers potential for cellulose and fiber resources.